SUMBANGAN PROGRAM ASISTENSI MENGAJAR DI STKIP WIDYA YUWANA DALAM TAHAP PERSIAPAN CALON GURU AGAMA KATOLIK - Christianus Freedus Yorifan; Albert I Ketut Deni Wijaya (Lembaga Penelitian STKIP Widya Yuwana, 2026)
College of teacher education (STKIP) Widya Yuwana has been implementing the Teaching Assistance Program since Academic Year (TA) in 2020/2021. This research aimed to analyze the contribution of the teaching assistance program for the preparation of prospective Catholic religious teachers and catechist at STKIP Widya Yuwana. The research was conducted using a qualitative method approach. Research data collection was carried out using both structured and individual interview techniques. The research informants were the students of STKIP Widya Yuwana who had carried out a teaching assistance program in a particular educational unit for one semester. The results of the research indicated that the teaching assistance program at STKIP Widya Yuwana provides a significant contribution to the development of teaching skills, the ability to innovate learning proces, and a valuable experience of adapting oneself to the new social and cultural environments.